Sensory characterization of pinni - a milk cereal based sweet using Quantitative Descriptive Analysis and Principal Component Analysis - Singh, Ravinder; Prasad, Writhdhama; Khamrui, Kaushik (Indian Journal of Dairy Science, 2019)
Pinni is a popular traditional milk-cereal based sweet of northern states of India viz., Punjab, Haryana and Delhi. Samples collected from Market QDA revealed a significant (p